Teaching Open Literacies - Croeser Sky (Cultural Science)
University teaching, particularly teaching with and about digital technologies, can play a role in developing and expanding open literacies. At the same time, we face a range of challenges as teachers. The managerial focus on measuring and quantifying teaching and learning outcomes within academia often works against the evidence on pedagogical best practice. Despite claims made about ‘digital natives’, we find that students of all ages frequently have difficulty sorting through the mass of information available online. It is not enough, as teachers, to simply provide content to students, or even to ‘engage’ students through gamified learning and other digitally supported teaching methods. To effectively support open literacies within university education we need to question institutionalized practices, including commitment to discipline canon and to a depoliticized, depersonalized approach to teaching. In order to be effective, I argue that our pedagogies must be diverse, context-dependent, and reflexive.